Efectos de un programa piloto de desarrollo cognitivo ‘teoría de la mente’ en tres niños con autismo: Componente emocional (2016)
Introduction. Theory of mind is defined as the capacity to predict, understand and act when faced with other people’s behaviour, their knowledge, their intentions, their emotions and their beliefs. It is proposed as a feasible alternative for establishing a programme adapted to the characteristics of children diagnosed with autism spectrum disorder. Case reports. The effect of a ‘theory of mind’ cognitive development pilot programme on the emotional skills of three children with autism spectrum disorder is reported. Case 1: 9-year-old boy, with scarce emotional identification and expression, as well as difficulties to hold fluent and coherent conversations. Case 2: 10-year-old boy, with mechanical, not very fluent language, and difficulties to start and maintain a conversation. Case 3: 8-year-old girl who presents deficits in the non-verbal communicative behaviours used in social interaction and difficulties to adapt to situations other than everyday ones. In the three cases there is an improvement in the emotional capacities following implementation of the programme; moreover, their parents, teachers or therapists perceived positive changes in the children’s adaptive skills. Conclusions. The methodological and structural aspects of the cognitive development programme were well-suited to the children with autism who took part in the research study. Due to the preliminary nature of this study, it is suggested that future research should utilise a larger sample and a double-blind design with randomised case-controls that allow the findings to be generalised. © 2016 Revista de Neurología.